Effects of Imipramine Treatment on δ-Opioid Receptors of the Rat Brain Cortex and Striatum - Varona, Adolfo; Gil, Javier; Saracibar, Gonzalo; Maza, Jose Luis; Echevarria, Enrique; Irazusta, Jon (Arzneimittelforschung, 2003)
Imipramine (CAS 113-52-0) is being utilized widely for the treatment of major depression. In recent years, there has been evidence of the involvement of the endogenous opioid system in major depression and its treatment. There is some evidence indicating that opioid receptors could be involved in the antidepressant mechanism of action. Regarding this topic, mood-related behavior of endogenous enkephalins seems to be mediated by δ-opioid receptors. In this work, the effects of subacute (5 day) and chronic (15 day) treatments of imipramine on the density and the affinity of the δ-receptors in the striatum and in the parietal and frontal cortices of the rat brain are described. Studied parameters (Bmax and Kd) were calculated by a saturation binding assay with the δ-opioid agonists [3H]-DPDPE (tyrosyl-2,6-3H(N)-(2-D-penicillamine-5-D-penicillamine)-enkephalin) as specific ligand and DSLET ([D-serine2]-D-leucine-enkephalin-threonine) as nonradioactive competing ligand. It was found that 15 days treatment significantly decreased the δ-opioid receptor density, without changing the affinity, in the frontal cortex of the rat brain. That decrease was confirmed by δ-opioid receptor immunostaining. These results suggest that δ-opioid receptors could play a role in the chronic action mechanism of imipramine.
Keywords: Antidepressants; CAS 113-52-0; Enkephalins; Imipramine, effects on δ-opioid receptors, rat brain; δ-Opioid receptors